2002
DOI: 10.1016/s0006-3495(02)75334-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State 19F-NMR Analysis of 19F-Labeled Tryptophan in Gramicidin A in Oriented Membranes

Abstract: The response of membrane-associated peptides toward the lipid environment or other binding partners can be monitored by solid-state NMR of suitably labeled side chains. Tryptophan is a prominent amino acid in transmembrane helices, and its (19)F-labeled analogues are generally biocompatible and cause little structural perturbation. Hence, we use 5F-Trp as a highly sensitive NMR probe to monitor the conformation and dynamics of the indole ring. To establish this (19)F-NMR strategy, gramicidin A was labeled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 103 publications
3
64
0
Order By: Relevance
“…Grage and coworkers have used [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] F-Trp within the membrane-associated peptide gramicidin A to investigate the conformation and dynamics of the tryptophan side chain within a lipid environment. [49] (αTfm)Ala was introduced into the peptaibol alamethicin by our group. Aib (aminoisobutyric acid, a non-fluorinated alanine analogue) at position 13 of alamethicin was substituted by (αTfm)Ala, thereby incorporating the fluorine label into the bend region of the alamethicin molecule, which is supposed to play a key role in the function of voltagedependent ion channels.…”
Section: F Nmr Spectroscopymentioning
confidence: 99%
“…Grage and coworkers have used [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] F-Trp within the membrane-associated peptide gramicidin A to investigate the conformation and dynamics of the tryptophan side chain within a lipid environment. [49] (αTfm)Ala was introduced into the peptaibol alamethicin by our group. Aib (aminoisobutyric acid, a non-fluorinated alanine analogue) at position 13 of alamethicin was substituted by (αTfm)Ala, thereby incorporating the fluorine label into the bend region of the alamethicin molecule, which is supposed to play a key role in the function of voltagedependent ion channels.…”
Section: F Nmr Spectroscopymentioning
confidence: 99%
“…To be able to determine the structure and orientation of a peptide from the 19 F chemical shift, the CSA tensor orientation in the molecule must be known. Such tensors have been determined from crystal studies of similar compounds, and can also be characterized in oriented membranes (110). For example, 4F-Phg was synthetically introduced at two positions of the cyclic ␤-sheet peptide gramicidin S, which was studied over a range of concentrations in oriented DMPC membranes (111).…”
Section: F Nmr On Peptidesmentioning
confidence: 99%
“…In some circumstances, it is possible to design the labeling pattern and experiments to measure internuclear distances between two 19 F sites or between 19 F and 13 C or 15 N sites. Prototype experiments have been performed on gram-icidin in aligned bilayers, 170 and recently Ulrich and co-workers 171 have studied a variety of 19 F labeled polypeptides in aligned bilayers. McDowell et al 172 have demonstrated that the combination of 19 F with 13 C labeling enables the measurement of REDOR experiments over relatively long ranges in unoriented samples with magic angle spinning.…”
Section: Additional Experimental Nmr Constraintsmentioning
confidence: 99%